THE IMPACT OF SOCIAL MEDIA AND VLOGGING ON SPEAKING SKILL DEVELOPMENT - Teshaboyeva Nafisa Zubaydulla qizi; Normuxammedova Sabrina Sardor qizi (Ustozlar uchun, 2025)
Social media has revolutionized communication in the modern era, influencing not only the way individuals interact socially but also the way they learn languages and develop speaking skills. With the advent of platforms such as YouTube, TikTok, Instagram, and Facebook, learners are exposed to authentic spoken content, diverse accents, various speaking styles, and real-world discourse in ways never before possible. In parallel, vlogging has emerged as a popular genre within social media that encourages individuals to speak, narrate, present, and express themselves in structured or spontaneous ways. As a result, social media and vlogging have profound impacts on the development of speaking skills for language learners across the globe.